IMPLEMENTASI TAFSIR SURAT AL-MUZAMMIL AYAT EMPAT DENGAN METODE QIRAATI - Nidhom, Khoirun; Ghianovan, Jaka; Abadi Siregar, Mahfuzo (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2021)
In practice reading the Qur'an there are many methods or procedures for being able to read the Qur'an properly and correctly. One of the many methods of reading the Qur'an is the Qirati method. The QABIATI method is the method of teaching and learning in the Qur'an in a tartil, taught and reading without spelling. In this paper the data obtained descriptively compiled with qualitative research methods. Referring to the meaning of tartil in the letter Al-Muzammil verse four in this paper explained that the Qirati method implements the interpretation of the letter Al-Muzammil verse four. Because the method that focuses on the rules of Tajwid also with the advantages of teachers who cannot carelessly make the quality of the good and true Qur'an reading